Driving school information system (DriSIS) - Mohd Haziq, Ishak (2012)
Driving School Information System (DriSIS) is a web based online system for any driving school. This system has several approaches. The first one is to driving school staff. This driving school staff needs to handle many students at one time. This will give problem in term of communicating with student for their driving class schedule or exam. Looking at this scenario, driving school have problem in communicating with their student if the number of student more than the available Instructors. Besides that they also need to handle the instructor in term of notification and appointment. This system will help the instructor to access student information and their driving lesson record. Others than that, the instructor also can get any important information regarding appointment or memo about their schedule from this system. And the last one is to students. Students can access their own data. Only registered student can have access to the database. The only method is through the official website that included in the system. Methodology used in developing this project is Waterfall Software development methodology. Phases that are included are requirement, system analysis, design, implementation and system testing and maintenance. At the end of this project, it is hope that Driving School Information System (DriSIS) can contribute to driving school operation to make it better and to cater best service.